Science a la Mode : Physical Fashions and Fictions. - Rothman, Tony (Princeton legacy library., 2014)
These iconoclastic and witty essays are about what happens when scientists jump on band-wagons. Tony Rothman applies creative skepticism to contemporary fashions in science, including the ""standard model"" Big Bang theory, geodesic domes, the concept of nuclear winter, and sociological applications of the second law of thermodynamics. ""Rothman proves himself an excellent communicator ... I am grateful to him for he has enlarged my vision, increased my understanding, and made me more aware of the beauty of the patterns and connections of all the world.""--Dick Kovan, New Scientist ""These s